The Religious and Psychological Behavior of Adolescents in View of the Big Five Personalities - Z, Zuraida; Maryana, M; Widari, Lis Ayu; Mahmud, Ihsan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
In adolescence, morals and religion are the most important part where some people argue that morals and religion can control the behavior of children who grow up at this time. Specifically to find out the level of belief in God during adolescence and to find out the causes of low belief in God during adolescence. The research method used in this study is a qualitative method, using a descriptive approach. The research design in this study is a literature review study. The library research data used are books and journals that are directly or indirectly related to the title of this research